Development of Teaching Materials to Improve Asmaul Husna's Calligraphy Writing Skills based on Rainbow Scratch Note Media for TPQ Baitul Haq Students - Salsabilla, Alfina; Nurrohim, Ahmad; Syakira, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The use of technology in education has become a must in the digital age to improve the quality of learning. One of the technologies used is learning media, which acts as an intermediary between teachers and students in understanding learning material. This paper discusses the use of Rainbow Scratch Notes as a learning medium in developing Asmaul Husna's calligraphy drawing skills at TPQ Baitul Haq. The research method used is Classroom Action Research (PTK) with qualitative and quantitative approaches. The results showed an improvement in students' skills, while increasing students' interest and motivation in learning to Read and Write Quran (BTQ). This medium provides an interactive and fun learning experience, allowing students to practice writing and reciting Quran verses more effectively. This media evaluation shows a high level of satisfaction from students and teachers. Thus, Rainbow Scratch Note is effectively used as a learning medium in developing Asmaul Husna's calligraphy drawing skills, as well as increasing the overall effectiveness of BTQ learning. This is an important step in enriching religious learning methods with innovative and interactive technological approaches.